Cerebrovascular accidents in adult patients with congenital heart disease. Issue 15 (16th July 2010) - Hoffmann, A; Chockalingam, P; Balint, O H; Dadashev, A; Dimopoulos, K; Engel, R; Schmid, M; Schwerzmann, M; Gatzoulis, M A; Mulder, B; Oechslin, E
Abstract : Objective: To investigate the prevalence and characteristics of cerebrovascular accidents (CVA) in a large population of adults with congenital heart disease (CHD). Methods and results: In a retrospective analysis of aggregated European and Canadian databases a total population of 23 153 patients with CHD was followed up to the age of 16–91 years (mean 36.4 years). Among them, 458 patients (2.0%) had one or more CVA, with an estimated event rate of 0.05% per patient-year. Permanent neurological sequelae were noted in 116 patients (25.3%). The prevalence of CVA in selected diagnostic categories was as follows: open atrial septal defect 93/2351 (4.0%); closed atrial or ventricular septal defect 57/4035 (1.4%); corrected tetralogy of Fallot 52/2196 (2.4%); Eisenmenger physiology 24/467 (5.1%); other cyanotic 50/215 (23.3%); mechanical prostheses (29/882 (3.3%). Associated conditions in patients with CVA were absence of sinus rhythm (25%), transvenous pacemakers (7%), endocarditis (2%), cardiac surgery (11%) and catheter intervention (2%), but with the exception of absent sinus rhythm these were not significantly more prevalent in patients with CVA. Conclusion: CVA are a major contributor to morbidity in this young population despite absence of classical cardiovascular risk factors. Although the prevalence of CVA in patients with CHD appears low, it is 10–100 times higher than expected in control populations of comparable age. Residua occur in a strong minority of patients. The subjects at highest risk are those patients with CHD with cyanotic lesions, in whom the prevalence is over 10-fold above the average.